Рассказы и сказки - Бианки Виталий Валентинович (Школьная библиотека, 2018)
Экземпляры: ДБ (20190617) / Инвентарный номер: 51079 / Цена: 95.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 59 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6